2003
DOI: 10.1186/1471-2105-4-29
|View full text |Cite
|
Sign up to set email alerts
|

MatGAT: An application that generates similarity/identity matrices using protein or DNA sequences

Abstract: Background: The rapid increase in the amount of protein and DNA sequence information available has become almost overwhelming to researchers. So much information is now accessible that high-quality, functional gene analysis and categorization has become a major goal for many laboratories. To aid in this categorization, there is a need for non-commercial software that is able to both align sequences and also calculate pairwise levels of similarity/identity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
184
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 759 publications
(184 citation statements)
references
References 9 publications
0
184
0
Order By: Relevance
“…1A). Amino acid sequence comparison using MatGat software (31) indicated that chIL-17RA shared ca. 46% identity with its human, mouse, and rat counterparts and 29.2 to 31.5% identity with trout, salmon, and zebrafish.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). Amino acid sequence comparison using MatGat software (31) indicated that chIL-17RA shared ca. 46% identity with its human, mouse, and rat counterparts and 29.2 to 31.5% identity with trout, salmon, and zebrafish.…”
Section: Resultsmentioning
confidence: 99%
“…Prediction of disulfide bond partners was performed using DiANNA 1.1 software (30). Homology analysis was performed using MatGat software (31).…”
Section: Animals and Infectionsmentioning
confidence: 99%
“…This software, provided as a supplement package by Deloger et al (31), was then used to trim the overlapping MUMs and to generate MUM index (MUMi) values for the genome relatedness comparison. The similarity/identity matrix between all 16S and 23S rRNA bifidobacterial gene sequences was calculated with MatGat, version 2.03 (Matrix Global Alignment Tool), using the BLOSUM 50 alignment matrix (32).…”
Section: Methodsmentioning
confidence: 99%
“…Signal peptide predictions were made using Signal P4.0 software (http://www.cbs.dtu.dk/services/SignalP) according to Petersen et al (42), and N-glycosylation sites were predicted using the NetNGlyc 1.0 server (http://www.cbs.dtu.dk/services/NetNGlyc) (R. Gupta, E. Jung, and S. Brunak, unpublished data). Amino acid homology comparisons were performed using the MatGAT package (version 2.02) (43). Phylogenetic trees were constructed from CLUSTAL W-generated alignments using the neighbor-joining (N-J) method within the MEGA (version 4.1) package (44).…”
Section: Methodsmentioning
confidence: 99%